Antecedents of Students’ Loyalty: the Case of an Open and Distance Learning Institution - Yon Rosli (2019)
Research on student loyalty has predominantly concentrated on traditional university setting and on full time students and very less concentrated on open distance learning universities where the students are part time students. The purpose of this research is to examine the relationship between the factors leading to student loyalty in open distance learning universities. Specifically, the objective of this research is to examine the relationship between Perceived Service Quality, Perceived E-Service Quality, and University Image as mediator on Student Loyalty in Open University Malaysia. Data was collected from students pursuing their studies at Open University Malaysia. Data was collected from sixteen learning centres throughout Malaysia. A purposive convenient sampling technique was used for this research where a sample size of 752 respondents was obtained. Analysis from the data indicated there was a positive significant relationship between Perceived Service Quality and University Image. Perceived Service Quality was also found to have a positive significant relationship with Student Loyalty. Similarly, it was also found that there was a positive significant relationship between Perceived E-Service Quality and University Image. Perceived EService Quality was also found to have a positive significant relationship with Student Loyalty. University Image was also discovered to act as a mediator for the relationship between Perceived Service Quality and Student Loyalty. Similarly University Image was also discovered to act as a mediator for the relationship between Perceived E-Service Quality and Student Loyalty. This research has provided a measurement scale specific to measuring service quality to open distance learning universities and facilitate in improving the marketing strategies in open distance learning universities. (Abstract by Author)